EVOLUTION OF COMMUNICATION SOCIOLOGY: SOCIAL MEDIA INTERVENTION IN THE REALITY CONSTRUCTION OF SECOND ACCOUNT PHENOMENON IN THE ERA OF DIGITAL SOCIETY - Muhammad Al-Haadi; Salwa Junisa; Aulia Irsalina; Najeeda Emira Chibro (Academic Solution Publisher, 2025)
This study examines the sociological evolution of communication in digital society by focusing on secondary accounts as strategic responses to social pressure on mainstream social media platforms. Using a qualitative methodology and a virtual ethnographic approach within a constructivist paradigm, the research explores how individuals construct and negotiate their social identities in digital spaces. Data were drawn from academic books, peer-reviewed journals, and scholarly articles, and were complemented by virtual observations and in-depth interviews with users of secondary accounts. Thematic analysis was employed to identify patterns related to digital identity and social interaction, while data validity was ensured through triangulation of observations, interview findings, and existing literature. The findings indicate that secondary accounts serve as important spaces for expressing authentic selves beyond the controlled personas presented on primary accounts. This practice reflects both tactical management of social visibility and ongoing negotiation between personal freedom and social conformity. Overall, the study highlights the dynamic and segmented nature of digital identity within contemporary social media ecosystems.